PENINGKATAN KETERAMPILAN GERAK DASAR LOKOMOTOR MELALUI PERMAINAN TRADISIONAL GOBAK SODOR PADA SISWA KELAS V SDN LABAN 02 KEC. MOJOLABAN - Sunanto, Rachmad; Gatot Jariono; Vera Septi Sistiasih; Nur Subekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research was conducted to determine the application and influence of the traditional game gobak sodor in improving basic locomotor movements in class V students at SDN Laban 02 Kec. Mojolaban and the benefits of research: 1. Improving basic locomotor movements for running, 2. Increasing the ability and professionalism of Physical Education teachers, 3. Increasing students' learning abilities. Classroom Action Research (PTK) is carried out in two cycles consisting of 4 stages, planning, action, observation and reflection. The results of the research show that the application of the traditional game gobak sodor improves basic locomotor running movements in class V students at SDN Laban 02 Kec. Mojolaban. From the results of observations of 20 students. In cycle I there were 10 students who received the